Effect of consumers' characteristics on attitude towards online shopping - Jadehkenari, Marzieh Zendehdel; Paim, Laily (Malaysian Consumer and Family Economics Association, 2015)
Thanks to the internet, the way of business operations and the way of interaction between producers and consumers have been significantly changed. As a business medium, the Internet enables firms to create environments with online interactions allowing consumers to obtain and assess information, evaluate purchase intention and directly do their purchases in a very convenient way. Moreover, replacing the traditional way of shopping behavior and habit of numerous consumers, online shopping is growing at a rapid rate in Malaysia. This study intends to examine the factors affecting consumers’ online shopping attitude in the country. The research suggests a framework for online shopping while taking into account different critical factors, known as the antecedents for online shopping in this country. Also, paying attention to the determinants of the attitude toward online shopping intention is essential for marketers to develop their marketing strategies to increase sales. This study examines the factors predicting students’ online shopping attitude at universities in the area of the Klang Valley in West Malaysia. In this research, the cluster sampling method was employed. The study showed that there is a significant and positive correlation between the subjective norm and integrity and ability and the attitude of online shoppers. However, there is no significant relationship with regard to benevolence.